Bilingual Learning for Language Development of Deaf Children in the Context of Intercultural Education - Anna Irasiak (University of Lower Silesia, 2015)
The article includes an analysis of issues concerning the question of intercultural pedagogy, i.e. the notions of multiculturalism and interculturalism, creating identity in the context of multiculturalism and multicultural and intercultural education. It also presents the situation of people with hearing impairment and the culture they create on the basis of sign language, a way of communication different from the dominant one, in relation with the culture of the dominant group, people who are perfectly able and use the phonic language. Coexistence of distinct cultures of unequal status in the same area has consequences for the education of a deaf child. One solution might be a method of bilingual teaching that enables unimpeded development (in particular language development) while passing on norms and values typical of the minority culture and acquiring general facts in a manner appropriate to the learner's needs.